Future smart cities: requirements, emerging technologies, applications, challenges, and future aspects. (October 2022) - Javed, Abdul Rehman; Shahzad, Faisal; Rehman, Saif ur; Zikria, Yousaf Bin; Razzak, Imran; Jalil, Zunera; Xu, Guandong
Abstract: Future smart cities are the key to fulfilling the ever-growing demands of citizens. Information and communication advancements will empower better administration of accessible resources. The eventual fate of the world's betterment lies in its urban environment advancement. The fast influx of individuals creates possibility, yet it additionally causes challenges. Creating sustainable, reasonable space in the world's steadily extending cities is tested confronting governments worldwide. The model of the smart cities rise, where the rights and well-being of the smart city citizens are assured, the industry is in action, and the assessment of urban planning from an environmental point of view. This paper presents a survey on analyzing future technologies and requirements for future smart cities. We provide extensive research to identify and inspect the latest technology advancements, the foundation of the upcoming robust era. Such technologies include deep learning (DL), machine learning (ML), internet of things (IoT), mobile computing, big data, blockchain, sixth-generation (6G) networks, WiFi-7, industry 5.0, robotic systems, heating ventilation, and air conditioning (HVAC), digital forensic, industrial control systems, connected and automated vehicles (CAVs), electric vehicles, product recycling, flying Cars, pantry backup, calamity backup and vital integration of cybersecurity to keep the user concerns secured. We provide a detailed review of the existing future smart cities application frameworks. Furthermore, we discuss various technological challenges of future smart cities. Finally, we identify the future dimensions of smart cities to develop smart cities with the precedence of smart living. Highlights: Analyze future smart cities' characteristics based on state-of-the-art technologies. Identifies and inspects the latest advancements in technology. Analyze the most feasible frameworks and their proficiency for FSC. Provide technology challenges identified in the literature. Provide future directions are identified to develop smart cities.